Vanillin: A Promising Biosourced Building Block for the Preparation of Various Heterocycles - Gendron, David (Frontiers in Chemistry, 2022)
The preparation of heterocyclic compounds often involves the use of petroleum-based or non-renewable sources. Considering the actual societal and environmental awareness towards sustainable chemistry, new and green sources of organic carbon are sought. In this regard, vanillin is a molecular building block that can be obtained from the depolymerization of lignin. Due to its different functional groups (hydroxyl, aldehyde and methoxy) vanillin can undergo a variety of reactions leading to various heterocycles such as pyrimidines, quinoxalines, imidazoles or thiazoles to name a few. This mini-review will focus on the preparation of accessible heterocycles building blocks from the vanillin moiety in regard to the medicinal, pharmaceutical, and material fields.